Estudio de prefactibilidad para la instalación de una planta de fabricación de bodys para bebés a base de algodón orgánico - Año Meza, Lisbeth (2020)
This project covers the preliminary study for the installation of a plant for the manufacture of a body with a custom design made from organic cotton using organic and biodegradable dyes and packaging materials, marketed electronically in Lima. To see the viability of this project we have conducted a study composed of different chapters. Chapter I contains the key points of the investigation, such as the problem, the objectives to be achieved and the hypothesis that serves as the basis for the investigation. Chapter II develops the market study to identify commercial viability, where the target market is determined is Lima, Arequipa and Ica. Likewise, we determine the demand of the project, we analyze the offer where we identify our main competitors, in order to develop the development strategies. Finally determine the sale price of S /. 55.00 In Chapter III we analyze the different possible locations for our plant. Therefore, a macro analysis was considered Chincha, Cañete and Lima; The districts of Lima were considered for the micro location analysis. In chapter IV we define the appropriate plant size, the market, productive resources, technology, investment and break-even point in order to cover our demand, resulting 300 m2. Chapter V details all the engineering of the project, which describes the production process, material balance, installed capacity and final disposal. Chapter VI determines the organizational structure with administrative, operational personnel and the necessary outsourcing. In Chapter VII, we will analyze the economic viability estimating investments, production costs, operational and financial budgets, to perform an economic and financial evaluation, obtaining a NPV of S/. 717,429, IRR of 52.9%, B / C of 2.65 and a PR of 3 years and 3 months. Finally, in the Chapter VIII develops the social evaluation of the project through indicators.